Editorial Vol.7(1-2) - Board, Editorial (Journal of NELTA Gandaki, 2024)
The Journal of NELTA Gandaki (JoNG) stands a prominent publication in the fields of English language teaching (ELT), teacher development, and teacher education. It serves as a valuable platform for EFL teachers from home and abroad to share their research and pedagogical skills through academic writing. We are delighted to present the seventh volume of the JoNG, a one-star rated peer-reviewed journal indexed in NepJOL published by the NELTA Gandaki Province Committee. The JoNG offers a diverse range of empirical and theoretical articles on EFL pedagogy, the integration of ICT and technology in ELT, and varied areas of English language and literature. We encourage readers for critical reading of the published manuscripts, gain fresh insights and contribute to the ongoing dialogues by sharing their experiences, skills, and expertise.